Cajanus cajan: a promissory high-nitrogen fixing cover crop for Uruguay - Berriel, Verónica; Perdomo, Carlos H. (Frontiers in Agronomy, 2023)
Cover crops can increase agricultural sustainability by protecting soil from erosion, increasing biodiversity, and symbiotically incorporating fixed nitrogen (N) into the soil. Nowadays, however, in Uruguay mostly grasses are planted in autumn to protect the soil from erosion. Another option is to study tropical legumes’ performance as cover crops, which can fix substantial amounts of nitrogen in short growing periods, thereby bridging the knowledge gap in Uruguayan agriculture. The main objective was to evaluate and compare the performance of six tropical legumes (Crotalaria juncea, Crotalaria spectabilis, Crotalaria ochroleuca, Cajanus cajan, Dolichos lablab, Mucuna pruriens) and the temperate legume Glycine max. The evaluation focused on aboveground biomass and the N mass derived from fixation (NmdFix), as well as other attributes; three field experiments were conducted on a southern Uruguay farm during the summers of 2017, 2018, and 2019. The growing cycle lengths for the cover crops in 2017, 2018, and 2019 were 117, 130, and 90 days, respectively. The results showed that when planting was done at late December (2017 and 2018 growing cycles), the species with the highest mean biomass yield were Crotalaria juncea (two year average 12.0 Mg ha-1) and Cajanus cajan (11.0 Mg ha-1), but Cajanus cajan (149 kg ha-1) more than doubled the NmdFix mass of Crotalaria juncea (57 kg ha-1). In 2018 biomass yields were much higher than in 2017, with Glycine max (20.0 Mg ha-1) yielding at a similar level to Crotalaria juncea and Cajanus cajan (20.5 and 18.7 Mg ha-1, respectively). Amounts of NmdFix, however, were much higher in Glycine max and Cajanus cajan (263 and 253 kg N ha-1, respectively), than in Crotalaria juncea (91 kg N ha-1). In 2019 planting had to be delayed until early February and only Glycine max maintained acceptable biomass and NmdFix levels. In conclusion, based on its fixing N potential, for late December sowings Cajanus cajan and Glycine max would be the most promising species for cover crop use, while for late January or early February sowings, only Glycine max would an option because the tropical species seriously impaired their productivity when grew longer into the cooler autumn temperatures.